Arthur$1 (Bs tooths - Brown, Marc Tolon (Boston : Little, Brown and Company, 1985)
Arthur, tired of being the only one in his class who still has all his baby teeth, waits impatiently for his loose tooth to fall out.
Keywords: Teeth -- Fiction; Animals -- Fiction